Fatal persistent methicillin-resistant Staphylococcus aureus bacteremia and vascular graft infections complicated with the formation of multiple abscesses despite aggressive medical therapy. (12th June 2015) - Shiba, Mikio; Yanai, Mitsuru; Maeda, Hideaki; Shiono, Motomi
A 40-year-old man underwent ascending aorta replacement for an acute type A aortic dissection. After the operations, methicillin-resistant Staphylococcus aureus was identified in sputum and blood cultures. Although anti-methicillin-resistant Staphylococcus aureus drugs were administered, most of the intermittent blood cultures remained positive. The focus of methicillin-resistant Staphylococcus aureus infection was not evident in the early stages, and no specific symptoms such as abscess or endocarditis were observed. However, abscesses in the brain, mediastinum and spleen were found 3 years after the operation. The minimum inhibitory concentration of vancomycin gradually increased from 1 to 4 µg/mL during the course of treatment. This case provides evidence for a potential role of combination therapy.